Experimental investigations on enhanced alternating-magnetic field-assisted finishing of stereolithographic 3D printing zirconia ceramics. Issue 24 (15th December 2022) - Sun, Zhiguang; Tian, Yebing; Fan, Zenghua; Qian, Cheng; Ma, Zhen; Li, Ling; Yu, Honglin; Guo, Jiang
Abstract: Zirconia ceramic components have great applications in the fields of medical, aerospace, and energy. Stereolithographic (SLA) 3D printing technology is widely employed for zirconia ceramic fabrication. However, the surface quality of manufactured components by direct SLA 3D printing is hard to meet stringent requirements of industrial application. In this work, an enhanced alternating-magnetic field-assisted finishing (A-MFAF) method was proposed for SLA printed zirconia ceramics. The A-MFAF was achieved using a flexible alternating-magnetic-field generator, integrating a rectangular magnetic pole and radial magnetic column. The novel finishing tool was fabricated to regulate finishing media behaviors for ensuring desirable finishing force. The unique construction of the magnetic field generator provided a controllable alternating magnetic field in the finishing zone. The magnetic control characteristics were investigated with finite element analysis (FEA). A serial of finishing experiments were carried out to verify the feasibility of the proposed A-MFAF method for SLA printed zirconia ceramics. The finishing efficiency with the developed magnetorheological shear thickening finishing (MSTF) media was improved by over 24% compared to that with the conventional magnetorheological finishing (MRF) fluids. The variation of surface roughness was qualitatively evaluated under different finishing conditions. The surface roughness of 89 nm was obtained from the initial 1.79 μm at 0.6 mm working gap and 700 r/min spindle rotational speed. Digital microscope, optical profiler and surface hydrophobicity measuring instrument were employed to investigate the surface characteristics of the finished SLA printed zirconia ceramics. Ultra-smooth surface with slight defects and deformations was obtained. The feasibility of A-MFAF method for the ultra-precision finishing of SLA printed zirconia ceramics was verified. Abstract : To further quantitatively evaluate the variation of magnetic flux density in the finishing zone with the rotation of the radial magnetic column. The magnetic flux density along line 1 of Fig. 2 (working gap: 0.6 mm) was calculated by FEA at different rotational positions of the radial magnetic column (rotation interval: 30°), as shown in Fig. 4. The continuous fluctuations between 0.06 T and 0.46 T of magnetic flux density in the finishing zone were found during one cycle of the radial magnetic column rotation. When the magnetic column was respectively rotated to 90° and 270°, the distribution of magnetic flux density along the measurement line was not uniform. This is because two inverse coupling effects (i.e. like charges repel each other, unlike charges attract) were sequentially excited under the relative rotation of the two magnetic poles with different magnetizing directions. It caused the magnetic field distribution in the finishing zone between the two magnetic poles to change drastically. In addition, the presence of the slots regularly changed the working gap between finished surface and the outside of the rotational radial magnetic column. It was observed that the variation value of the magnetic flux density was different from that at the same rotation interval. This was bound up with the position of the interaction between the radial magnetic column and the rectangular magnetic pole. Therefore, the alternating magnetic field was generated by the rotation of the radial magnetic column. The large finishing forces were generated by the formed alternating magnetic field based on Eq (1). Moreover, this also accelerated the cyclic replacement of MSTF media. Compared with the electromagnetic coil (EMC), alternating magnetic field with the excitation of permanent magnetic yoke greatly simplified the structure of magnetic field generation apparatus and solved the problems of severe heat generation and weak magnetic flux density [39 ].